OPTIMALISASI RUANG PUBLIK GUNA MENINGKATKAN PENDAPATAN DI BANDAR UDARA INTERNASIONAL YOGYAKARTA - Nadia Shifa Azzahra; Agoes Soebagio; Lina Rosmayanti (FTK UNSURYA, 2026)
This research aims to optimize the utilization of the landside area at Yogyakarta International Airport as a commercial space, to increase non-aeronautical revenue by organizing events. This research employs a qualitative approach with descriptive methods, utilizing data collection techniques that include field observations, interviews, and documentation, which are validated through source triangulation. The results of the analysis show that the location of Tugu Malioboro, which is the land area of Yogyakarta International Airport, has great potential to be developed as an interactive and productive zone, but its utilization is still limited due to rent constraints and a lack of collaborative marketing strategies. Through the Value Proposition Canvas approach, it was found that organizing events with the support of MSMEs, local governments, and sponsors was able to create added value for service users and local businesses, while strengthening the airport's image as a center of economic and cultural activities. This strategy contributes to increasing non-aeronautical revenue and strengthening the airport's socio-economic functions.